Mesoscale Domains and Nature of the Relaxor State by Piezoresponse Force Microscopy - Shvartsman, V. V.
Ferroelectric relaxors continue to be one of the most mysterious solid-state materials. Since their discovery by Smolenskii and coworkers, there have been many attempts to understand the properties of these materials, which are exotic, yet useful for applications. On the basis of the numerous experimental data, several theories have been established, but none of them can explain all the properties of relaxors. The recent advent of piezoresponse force microscopy (PFM) has allowed for polarization mapping on the surface of relaxors with subnanometer resolution. This development thus leads to the question of whether the polar nanoregions that contribute to diffuse X-ray scattering and a range of macroscopic properties can be visualized. This review summarizes recent advancements in the application of PFM to a number of ferroelectric relaxors and provides a tentative explanation of the peculiar polarization distributions related to the intriguing physical phenomena in these materials.